Efektivitas Layanan Perpustakaan Sekolah di SLB Wacana Asih Padang - Arumi, Ratih; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
This article discuss about library effectiveness service in different ability school of Wacana Asih Padang West Sumatera Indonesia. The conclusion based on analysis data is First the library service by librarian in different ability school of Wacana Asih Padang not yet to do, because many student a little get and not use a service library. Second still find a trouble in service library activities in different ability school of Wacana Asih Padang, like us less attention and miss understanding from the librarian about library service, less facility and estimate fund. And then less amount of service in the library it make not effective for service. Third the effort that can be doing to solve the problem is the librarian must get a special training and suggestion to more care about library service. To improve the facility and estimate fund, to get a better library effectiveness service for student.Â Keyword: effectiveness, service, different ability school